THE ROLE OF TECHNOLOGY IN MODERN ISLAMIC EDUCATION MANAGEMENT - Loso Judijanto; Arnadi (International Journal of Teaching and Learning, 2025)
The role of technology in modern Islamic education management is crucial in improving administrative efficiency and teaching quality. By utilising school management applications and other digital platforms, Islamic education institutions can manage administrative processes, student data, and exam administration more effectively and securely. Technology also allows for the diversification of teaching methods through the use of digital resources such as learning videos, e-books and interactive materials, thereby reaching students' various learning styles and enriching their learning experience. However, the integration of these technologies must be done carefully to ensure that they are compatible with Islamic values. Challenges such as the selection of Shariah-compliant platforms, adequate infrastructure, and the technical skills of teachers and staff must be addressed. Support from all stakeholders, including the government, educational institutions, and the community, is needed to support the successful implementation of this technology. With a wise and measured approach, technology can be an invaluable tool to improve the quality and efficiency of modern Islamic education management.